2023
DOI: 10.1101/2023.03.06.531355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNAJB8 oligomerization is mediated by an aromatic-rich motif that is dispensable for substrate activity

Abstract: SUMMARYJ-domain protein (JDP) molecular chaperones have emerged as central players that maintain a healthy proteome. The diverse members of the JDP family function as monomers/dimers and a small subset assemble into micron-sized oligomers. The oligomeric JDP members have eluded structural characterization due to their low-complexity, intrinsically disordered middle domains. This in turn, obscures the biological significance of these larger oligomers in protein folding processes. Here, we identified a short, ar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
(305 reference statements)
0
3
0
Order By: Relevance
“…The equivalent peptide in DNAJB6b can be hypothesized to be 153 GFSSFD 158 , which indeed is mostly exposed when DNAJB6b is in its extended state. It was found that for DNAJB8, mutations in this peptide did abolish self-oligomerization and lead to DNAJB8 monomerization; this monomeric DNAJB8, however, did retain wildtype activity in terms of substrate binding and chaperone function [53]. This would imply that substrate-binding and self-oligomerization are driven by the same S/T domain, and that monomers are the functional chaperone moieties, and self-oligomerization may only happen at high concentrations in the absence of clients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The equivalent peptide in DNAJB6b can be hypothesized to be 153 GFSSFD 158 , which indeed is mostly exposed when DNAJB6b is in its extended state. It was found that for DNAJB8, mutations in this peptide did abolish self-oligomerization and lead to DNAJB8 monomerization; this monomeric DNAJB8, however, did retain wildtype activity in terms of substrate binding and chaperone function [53]. This would imply that substrate-binding and self-oligomerization are driven by the same S/T domain, and that monomers are the functional chaperone moieties, and self-oligomerization may only happen at high concentrations in the absence of clients.…”
Section: Discussionmentioning
confidence: 99%
“…Another still open question relates to the role of self-oligomerization of the DNAJB6-subgroup. A recent study on DNAJB8 revealed that this is related to a specific peptide ( 147 AFSSFN 152 ) within the S/T rich region [53]. The equivalent peptide in DNAJB6b can be hypothesized to be 153 GFSSFD 158 , which indeed is mostly exposed when DNAJB6b is in its extended state.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting unaddressed question is the role of DNJAB8 oligomerization. DNAJB8 and the structurally similar DNAJB6 form a distribution of oligomeric, dimeric, and monomeric stables, while DNAJB1 forms dimers [26,42,43].…”
Section: Discussionmentioning
confidence: 99%